ANTIMICROBIAL EFFECTIVENESS OF APPLE CIDER VINEGAR IN THE GROWTH OF Staphylococcus epidermidis and Propionibacterium acnes - Imam Prabowo; Arifa Shaliha; Oktania Sandra Puspita (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2022)
Acne is a skin disease caused by Propionibacterium acnes, Staphylococcus epidermidis-, and Staphylococcus aureus-induced inflammation. Apple cider vinegar contains antibacterial compounds such as acetic acid, chlorogenic acid, polyphenols, alkaloids, flavonoids, and glycosides. This study is conducted to determine the effectiveness of antibacterial compounds contained in apple cider vinegar against the growth of S.epidermidis and P.acnes, in vitro. The study used the disc diffusion method by utilizing the Mueller Hinton Agar medium. The apple cider vinegar inhibition zone was formed at the concentration of 25%, 50%, 75%, and 100% against the growth of P.acnes, whereas the inhibition zone against S.epidermidis was formed at the concentration of 50%, 75%, and 100%. The highest inhibition zone against P. acnes was 8,825 mm and against S.epidermidis was 3,725 mm at the concentration of 75%. Test results One-way ANOVA on P.acnes and Kruskal Wallis to S.epidermidis obtained (p) <0,005. This study concludes the effectiveness of apple cider vinegar in inhibiting the growth of P. acnes and S. epidermidis, where the effectiveness against P. acnes was stronger than against S. epidermidis.